Profit-Loss Sharing Contract as an Alternative to Solve Unemployment in Sudan through Investment in Livestock Breeding - Mahmoud Mohamed Ali Mahmoud Edris; Mohamed Sharif Bashir; Yusuf Sani Abubakar (ADDIN, 2023)
The profit-loss sharing (PLS) or Mudārabah is an Islamic contract in which one side provides capital and the other side provides work. Profits are to be shared in the proportion that was agreed upon before the contract was implemented. This paper aims to highlight the role of the Mudārabah contract in financing livestock projects, and its use in solving the problem of unemployment in Sudan, where livestock breeding is a productive activity that provides employment opportunities and increases the incomes of the workers, and increases the rates of economic growth, especially since Sudan is ranked among the richest Arab and African countries with its livestock and agricultural wealth, and there is a large number of the population of Sudan working in the agricultural sector including the animal and plant subsectors. A large number of Sudan’s population works in the agricultural sector. The paper also intends to examine the applications of the Mudārabah contract as an investment alternative that can be more effectively utilized in providing employment opportunities for university graduates and job seekers in Sudan. a descriptive-analytical approach was used to define the Mudārabah concept and show the types of its application, and the methods of employing it to finance livestock projects in Sudan. The paper reached several results, the most important of which is that Mudārabah, such as in the Prophet’s practice and its contemporary applications, is one of the most significant investment formulas that can be used to finance productive projects in the livestock sector, especially small and medium-sized enterprises in the field of livestock breeding in Sudan.